ANALISIS LITERATUR PENGGUNAAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN PAI - Eka Dwi Ningsih; Santiani Santiani (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the application of the Discovery Learning model in learning Islamic Religious Education (PAI). This model is believed to improve student activeness, learning outcomes, and critical and analytical thinking skills. This research uses the library research method by analyzing various literatures relevant to the topic. The results showed that Discovery Learning is effective in improving students' understanding of PAI materials through active involvement in the learning process. In addition, this model is able to develop students' thinking skills in understanding religious concepts deeply and contextually. However, its implementation still faces several challenges, such as time constraints, facilities, and teachers' understanding in applying the model optimally. In conclusion, Discovery Learning has the potential to make a significant contribution to PAI learning, but it needs support from technical and pedagogical aspects to achieve maximum results.